Advancing a Baradian perspective on the field of identity work: : An empirical analysis of the complex discourse-materiality identity construction - Dille, Maria Hvid (Communication & Language at Work, 2020)
Conceptualizing identity in processual terms as identity work has long been acknowledged within the broad field of critical management and organization studies. However, recent studies show that the process by which identities evolve is still under-explored. Although extant research has considered how discourse and other symbolic means play a part in this process, this article expands such perspectives by foregrounding the relationality of discourse-materiality in identity construction processes. Using the example of an empirical analysis taken from a case study within education in Denmark, the author examines the process of identity construction by considering the ways in which discourse-materiality works to perform identities. The author combines insights from new materialist thinking with organizational discourse studies in the development of an analytics to approach the process of identity construction – coined as identity intra-activity. In doing so, the article demonstrates how an informal middle-management positioning of selected teachers is performed within its organization. By advancing the notion of identity intra-activity, the findings enable an understanding of identity work as materialized by multiple discursive-material and embodied resources – all enacted in/through the teachers’ practices – creating a petri dish for examining the co-constitutive role of discourse-materiality and enabling new ways of thinking about identity work.